Neurodevelopment of preterm infants with glucose and sodium abnormalities - Hui-Ying Yang; Cheng-Han Lee; Hsiao-Neng Chen; Lon-Yen Tsao; Jia-Yuh Chen; Yu-Jun Chang; Chien-Chou Hsiao (Elsevier, 2021)
Background: Blood glucose and serum sodium abnormalities in very low birth weight infants may cause increased morbidity and mortality, but data regarding the long-term outcomes are limited. This study aimed to investigate the association between the peak and nadir blood glucose and serum sodium levels and neurodevelopmental outcomes in very low birth weight infants. Methods: A single-center retrospective medical record of 284 infants with birth weight<1500 g born between February 1, 2011 and January 31, 2015 was reviewed. We analyzed the correlation between peak and nadir blood glucose and serum sodium levels during hospitalization and Bayley Scales of Infant and Toddler Development, third edition at 6, 12, and 24 months of corrected age. Results: A total of 284 very low birth weight premature infants were eligible, and 223, 208, and 188 patients were assessed at 6, 12, and 24 months of corrected age, respectively. Multiple linear regression analysis with generalized estimating equations showed that the BSID-III cognitive scores were significantly lower in the peak serum sodium group when sodium was ≧150 mmol/L (95% confidence interval −11.681 to −0.822) than when sodium did not exceed 150 mmol/L. Conclusion: A peak serum sodium of ≧150 mmol/L is associated with poor cognitive outcomes in very low birth weight infants. Further studies are necessary to determine if this association is causal or an expression of disease severity.